2018
DOI: 10.3233/isp-180147
|View full text |Cite
|
Sign up to set email alerts
|

CFD, potential flow and system-based simulations of fully appended free running 5415M in calm water and waves

Abstract: The seakeeping ability of ships is one of the aspects that needs to be assessed during the design phase of ships. Traditionally, potential flow calculations and model tests are employed to investigate whether the ship performs according to specified criteria. With the increase of computational power nowadays, advanced computational tools such as Computational Fluid Dynamics (CFD) become within reach of application during the assessment of ship designs. In the present paper, a detailed validation study of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Therefore, the time history of the roll, pitch, and heave motions, which are indirect to the mooring system, were mainly investigated to find out the period and magnitude of the wave-induced motions before reflected waves. In addition, the seakeeping test results of 5415M in beam and head seas by Toxopeus et al 17 were also compared to the present numerical analysis.…”
Section: Motion Response In Regular Wavesmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the time history of the roll, pitch, and heave motions, which are indirect to the mooring system, were mainly investigated to find out the period and magnitude of the wave-induced motions before reflected waves. In addition, the seakeeping test results of 5415M in beam and head seas by Toxopeus et al 17 were also compared to the present numerical analysis.…”
Section: Motion Response In Regular Wavesmentioning
confidence: 99%
“…“Aqwa_Set” and “Aqwa_Des.” mean numerical analysis results with the weight setting of “model (set)” and “model (design)” in Table 4 respectively. The study of Toxopeus et al 17 corresponds to “Aqwa_Des.” Because of the difference in GM T between the two weight distribution conditions, the roll motion difference was recognizable. The roll damping of the numerical analysis of 5415M was adjusted to fit with the seakeeping experiments, and the magnitude was 0.011 Nms/°.…”
Section: Seakeeping Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the WIM of the buoy is dominated by inertial and viscous effects of the hull, and that the results of coupled study on free-decay and wave-induced motions match well with model testing. In a similar study, Toxopeus et al [36] conducted some CFD simulations under waves and calm water using a self-propelled free running 5415M ship model and presented some motion response distributions. Bandringa et al [37] presented a CFD investigation which was validated using a linked CFD-dynamic mooring model for simulating the behaviour of a shallow water CALM buoy in extreme waves.…”
Section: Introductionmentioning
confidence: 99%